Escape : Waldo Engels, Gielo Thiry, Jacques Vandecasteele. - Engels, Waldo; Thiry, Giedo; Vandecasteele, Jacques ([S.l.] : [s.n.])
Teksten : Giedo Thiry, Schilderijen + objecten : Waldo Engels, Foto's : Jacques Vandecasteele
Biog., ind. tent., gr. tent. vdeo,... p. 80-82
Engels
Nederlands
boek
Keywords: Engels, Waldo; Vandecasteele, Jacques